ANALISIS PERANAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN DI KABUPATEN BANTAENG - Jamal, Miftahul Nur Jannah (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the role of the agricultural sector in supporting economic growth in Bantaeng Regency. A scientific approach to economic decision-making was employed, with data obtained from the Central Bureau of Statistics of Bantaeng Regency and the Department of Agriculture of Bantaeng Regency. Data collection techniques included interviews, online references, and the use of quantitative tools with computer software. The analysis applied a descriptive quantitative method, which involves explaining the problem and examining data using numerical calculations and statistical formulas. The results of the study show that: (1) the correlation coefficient is 0.739, indicating a strong relationship between agricultural production and economic growth in Bantaeng Regency; (2) the R-square value is 0.546, meaning that 55% of economic growth is influenced by agricultural production variables, while the remaining 45% is affected by other factors; and (3) the calculated t-value of 2.688 is greater than the t-table value of 1.943. This result confirms that agricultural production has a positive and significant effect on the economic growth of Bantaeng Regency.